Factors associated with generalized anxiety disorder in adolescents with cultural diversity: secondary data analysis - Dong-Hee Kim; Yujin Kim (BMC Public Health)
Abstract Background The number of culturally diverse adolescents in South Korea has reached 290,000 and is increasing every year; however, they still represent only 2.5% of the total adolescent population in middle and high schools, making them a minority. Adolescents experiencing cultural diversity are psychologically vulnerable because they grow up in bicultural environments and experience prejudice. Given the nature of generalized anxiety disorder, which can be exacerbated by stress, these adolescents may face an increased risk of developing the disorder not only because of developmental stress but also because of the stress of cultural adaptation. To identify the prevalence of generalized anxiety disorder among adolescents with cultural diversity, we analyzed related factors. Based on the results, strategies have been proposed to reduce anxiety in adolescents with cultural diversity and generalized anxiety disorders. Methods This study used data from the 16th − 18th Korea Youth Risk Behavior Survey. Factors associated with generalized anxiety disorders were identified based on the social determinants of the health framework. Statistical analyses were conducted using IBM SPSS 25.0, and statistical methods were used for complex samples. Results Among adolescents with cultural diversity, 12.8% exhibited generalized anxiety disorders. Among the structural factors, economic status, mother’s education level, and gender were significantly associated with the disorder, whereas among the psychosocial factors, suicidal ideation, depressive mood, loneliness, perceived stress level, and subjective health status were significant factors influencing it. Conclusion The factors identified in our research can be used as a resource for the early identification of culturally diverse adolescents who are vulnerable to generalized anxiety disorders. To prevent generalized anxiety disorder among adolescents with cultural diversity, school or community nurses can implement interventions to reduce loneliness or stress management programs.